Body and meat characteristics of young bulls from Zebu Goudali of Cameroon and its crosses with the Italian Simmental. Issue 1 (2nd January 2018) - Bessong Ojong, Willington; Saccà, Elena; Corazzin, Mirco; Sepulcri, Angela; Piasentier, Edi
Abstract: The aim of this trial was to compare the growth performance and meat yield and composition of SimGoud (Italian Simmental × Goudali, SG) crossbreed young bulls with those of pure Goudali (G) breed. Twenty-five G and 25 SG, from 20 to 41 months, reared together in Cameroon on native pasture were considered. Body size, growth and meat composition were compared. The SG crosses were more sized than the coetaneous pure G, having almost all body dimensions and mass index higher than G. Moreover, SG showed higher body weight at farm and ante-mortem than G, with about four times higher growth rate, but showed a marked loss of weight during transfer to slaughterhouse and lairage time. SG showed higher carcass weight and killing out percentage, in addition to a higher weight of rib steak and ribeye muscle at eighth–ninth rib section level than G. Despite the greater growth, differences between G and SG in beef proximate composition were not found. Genotype had a limited effect on fatty acids profile. However, G beef had greater CLA level, but lower MUFA content than SG. The study showed that G pure breed has much lower in vivo and slaughter performance than their crosses with the Italian Simmental breed, even if the meat composition was not different between the two genotypes. Conversely, despite similar pH of meat, G was more adaptable than SG to the severe transport condition and to the prolonged lairage time.